The Effects of Capsaicin on Gastrointestinal Cancers - Popescu, George Denis Alexandru (Molecules, 2020)
Gastrointestinal (GI) cancers are a group of diseases with very high positions in the ranking of cancer incidence and mortality. While they show common features regarding the molecular mechanisms involved in cancer development, organ-specific pathophysiological processes may trigger distinct signaling pathways and intricate interactions with inflammatory cells from the tumoral milieu and mediators involved in tumorigenesis. The treatment of GI cancers is a topic of increasing interest due to the severity of these diseases, their impact on the patients’ survivability and quality of life, and the burden they set on the healthcare system. As the efficiency of existing drugs is hindered by chemoresistance and adverse reactions when administered in high doses, new therapies are sought, and emerging drugs, formulations, and substance synergies are the focus of a growing number of studies. A class of chemicals with great potential through anti-inflammatory, anti-oxidant, and anti-tumoral effects is phytochemicals, and capsaicin in particular is the subject of intensive research looking to validate its position in complementing cancer treatment. Our paper thoroughly reviews the available scientific evidence concerning the effects of capsaicin on major GI cancers and its interactions with the molecular pathways involved in the course of these diseases.